2013
DOI: 10.1017/s0031182013000012
|View full text |Cite
|
Sign up to set email alerts
|

BnSP-7 toxin, a basic phospholipase A2 from Bothrops pauloensis snake venom, interferes with proliferation, ultrastructure and infectivity of Leishmania (Leishmania) amazonensis

Abstract: This paper reports the effects of BnSP-7 toxin, a catalytically inactive phospholipase A2 from Bothrops pauloensis snake venom, on Leishmania (Leishmania) amazonensis. BnSP-7 presented activity against promastigote parasite forms both in the MTT assay, with IC50 of 58.7 μg mL(-1) of toxin, and a growth curve, inhibiting parasite proliferation 60-70% at concentrations of 50-200 μg mL(-1) of toxin 96 h after treatment. Also, the toxin presented effects on amastigotes, reducing parasite viability by 50% at 28.1 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 41 publications
(57 reference statements)
2
36
0
13
Order By: Relevance
“…The venom of Viperidae snakes, in general, exhibit more pronounced leishmanicidal activity than that exhibited by B. marajoensis venom [35,70,71]. Both enzymatically inactive and active PLA 2 s from bothropic venoms have shown activity against several species of Leishmania similar to the present study [27][28][29][30]37]. Studies addressing the trypanocidal activity of svPLA 2 s are scarce, but other components of these venoms are being investigated.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The venom of Viperidae snakes, in general, exhibit more pronounced leishmanicidal activity than that exhibited by B. marajoensis venom [35,70,71]. Both enzymatically inactive and active PLA 2 s from bothropic venoms have shown activity against several species of Leishmania similar to the present study [27][28][29][30]37]. Studies addressing the trypanocidal activity of svPLA 2 s are scarce, but other components of these venoms are being investigated.…”
Section: Discussionsupporting
confidence: 69%
“…In three studies, PLA 2 s were isolated from B. brazili, B. mattagrossensis and B. moojeni venoms and their antiparasitic effects were checked against several different species of Leishmania [27][28][29]. Additionally, a non-catalytic PLA 2 isolated from Bothrops pauloensis venom, BnSP-7 inhibited the proliferation of L. amazonensis promastigotes and amastigotes and also caused morphological changes in the parasites [30].…”
Section: Introductionmentioning
confidence: 99%
“…Screening of a panel of toxins and antimicrobial peptides (AMPs) under axenic conditions revealed that one of them, a basic phospholipase A2 (PLA 2 ) from the Bothrops pauloensis snake venom, called BnSP-7, caused apoptosis-like cell death of the parasites upon the addition of the stabilizing ligand. Noticeably, this toxin has previously been demonstrated to kill L. amazonensis promastigotes in vitro, as well as to delay the amastigote-to-promastigote differentiation, to induce ultrastructural changes in promastigote morphology, and to reduce virulence [23]. The data presented here are complementary to the previous findings.…”
supporting
confidence: 86%
“…Com relação a suas propriedades farmacológicas, esta enzima induz necrose de fibras musculares, edema, libera creatina quinase do músculo gastrocnêmico de camundongos e apresenta atividade bactericida sobre Escherichia coli (RODRIGUES et al, 1998;SOARES et al, 2000;MAGRO et al, 2003) antiparasitária contra Leishmania amazonensis (NUNES et al, 2013) e Toxoplasma gondii (BORGES et al, 2016), dentre outras atividades (RODRIGUES et al, 2015). LOMONTE et al, 2003;FERNADES et.…”
Section: -Leishmanioseunclassified
“…A fim de verificar a capacidade de anticorpos IgY anti-BnSP-7 para neutralizar os efeitos de PLA2s, o nosso próximo passo foi avaliar a neutralização da citotoxicidade induzida por BnSP-7 para células C2C12. A BnSP-7 é uma PLA2 capaz de induzir edema e necrose de fibras musculares, liberando creatina quinase do músculo gastrocnêmio de camundongos, apresentando atividade bactericida contra Escherichia coli (RODRIGUES et al, 1998;SOARES et al, 2000;MAGRO et al, 2003;OLIVEIRA et al, 2009) e ação antiparasitária (NUNES et al, 2013;BORGES et al, 2016), entre outras atividades (RORIGUES et al, 2015).…”
Section: -Os Anticorposunclassified